2005 European Conference on Power Electronics and Applications 2005
DOI: 10.1109/epe.2005.219617
|View full text |Cite
|
Sign up to set email alerts
|

Properties, simulation and experimental investigation of the series-parallel active power filters

Abstract: In this paper introduced calculate method of active power filters passive components, simulation and experimental researches results of the series-parallel active power filter. Authors especially occupy oneself with analysis power flow between both active filters in UPQC system and nonlinear load. This problem is according to authors very important, because it makes possible to find optimum configuration of the hybrid UPFC and power of the additional sources elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In [127], authors have used fault current limiter to reduce the UPQC rating particularly by limiting the excessive current during the event of a fault. Finally, it is found that throughout the development phases of UPQC, researchers have given equal importance to evaluate the control algorithm and overall UPQC system performance by experimental investigation [11], [14], [22], [23], [26], [33], [40], [42], [51], [52], [56], [57], [60], [63], [75], [80], [81], [89], [94], [97], [107], [109], [114], [116]- [118], [120], [129], [143]- [145], [147], [150], [155]- [157], [159], [161], [163], [164], [167], [168]. A 250-kVA UPQC system is developed at the Centre for the Development of Advanced Computing (C-DAC), Thiruvananthapuram, India [75].…”
Section: Control Techniques For Upqcmentioning
confidence: 99%
See 1 more Smart Citation
“…In [127], authors have used fault current limiter to reduce the UPQC rating particularly by limiting the excessive current during the event of a fault. Finally, it is found that throughout the development phases of UPQC, researchers have given equal importance to evaluate the control algorithm and overall UPQC system performance by experimental investigation [11], [14], [22], [23], [26], [33], [40], [42], [51], [52], [56], [57], [60], [63], [75], [80], [81], [89], [94], [97], [107], [109], [114], [116]- [118], [120], [129], [143]- [145], [147], [150], [155]- [157], [159], [161], [163], [164], [167], [168]. A 250-kVA UPQC system is developed at the Centre for the Development of Advanced Computing (C-DAC), Thiruvananthapuram, India [75].…”
Section: Control Techniques For Upqcmentioning
confidence: 99%
“…During the system dynamic conditions, for example, sudden load change, voltage sag, the dc-link feedback controller should respond as fast as possible to restore the dc-link voltage at set reference value, with minimum delay as well as lower overshoot. The proportional-integral (PI)-regulator-based dc-link voltage controller is simple to implement and hence widely used by the researches [12]- [14], [16]- [20], [22], [23], [26]- [33], [36], [38], [40], [42], [46]- [48], [50], [54], [56], [60], [61], [64], [67], [68], [75]- [77], [81]- [84], [88]- [90], [92], [94], [95], [100], [103]- [105], [108], [109], [111]- [114], [116], [117], [119], [122], [124], [126]- [128], [130]- …”
Section: Upqc-state Of the Artmentioning
confidence: 99%
“…The aim of p-q control strategy is to find an effective strategy to compensate nonlinear loads using active power filters. Initially it was applied to balanced three-phase three-wire systems (3p3w) and then it was extended to unbalanced four-wire systems [18], [20], [21], [56], [61], [71], [92], [110], [116], [131], [133], [134], [136], [144], [146], [159], [161], [165], [167], [173], [180][181][182][183], [187], [188], [190], [202], [203], [213], [216].…”
Section: Instantaneous Reactive Power Theory (P-q Theory)mentioning
confidence: 99%